2014
DOI: 10.1161/atvbaha.114.303416
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Deletion of Phospholipase D2 Reduces Hypoxic Response and Pathological Angiogenesis

Abstract: A ngiogenesis involves complex endothelial cell (EC) behaviors, such as proliferation, survival, migration, and tube formation. The most important stimulus promoting angiogenesis is tissue hypoxia. Hypoxia mediates several processes in ECs that are required for each step of angiogenesis.1 Hypoxia-induced angiogenesis is closely related to pathological situation. The dysregulation of these EC behaviors and thus abnormal angiogenesis are critically associated with hypoxia-induced pathological angiogenesis that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 45 publications
(33 reference statements)
0
20
0
1
Order By: Relevance
“…Metastasizing tumor cells also need to interact with platelets to achieve efficient colonization at distant sites [57], and this is hindered in mice lacking PLD1 due to the blunted platelet activation described above; hence there are at least two roles for PLD1 in the tumor environment [31]. Related roles for PLD2 have also been described in hypoxia-induced Hif1-α expression and VEGF secretion by endothelial cells, which similarly results in a reduction of tumor neovascularization and growth when PLD2 is absent, although to a lesser extent than in the absence of PLD1 [58]. Inhibiting both PLD1 and PLD2 may both address redundancy and target non-overlapping roles as well.…”
Section: Therapeutic Opportunities For Pld Inhibitionmentioning
confidence: 99%
“…Metastasizing tumor cells also need to interact with platelets to achieve efficient colonization at distant sites [57], and this is hindered in mice lacking PLD1 due to the blunted platelet activation described above; hence there are at least two roles for PLD1 in the tumor environment [31]. Related roles for PLD2 have also been described in hypoxia-induced Hif1-α expression and VEGF secretion by endothelial cells, which similarly results in a reduction of tumor neovascularization and growth when PLD2 is absent, although to a lesser extent than in the absence of PLD1 [58]. Inhibiting both PLD1 and PLD2 may both address redundancy and target non-overlapping roles as well.…”
Section: Therapeutic Opportunities For Pld Inhibitionmentioning
confidence: 99%
“…In a human breast cancer xenograft model, it was shown that increased PLD2 expression in tumor cells suppresses apoptosis, ultimately facilitating tumor growth and chemoresistance ( 68 ). PLD2 may also play roles in the tumor environment similar to those previously reported for PLD1 ( 39 ), because PLD2 ablation from endothelial cells suppresses their hypoxiainduced Hif1-␣ expression and VEGF secretion, reducing proximal tumor neovascularization and growth ( 67 ). Although the overall expression levels of PLD2 may vary in tumors, there is a signifi cant correlation between PLD2 expression level and tumor size ( P < 0.05), as well as with survival of patients with colorectal carcinoma ( P < 0.05) ( 78 ).…”
Section: Pld3mentioning
confidence: 55%
“…Specific pathogen-free Villin-Cre mice (on the C57BL/6 genetic background) were purchased from the Jackson Laboratory. Pld2 floxed mice were generated as previously described 53 . The Pld2 IEC KO mice were generated by breeding Pld2 fl/fl mice with Villin-Cre mice.…”
Section: Methodsmentioning
confidence: 99%